2012
DOI: 10.1017/s0007114512001341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abomasal infusion of flaxseed (Linum usitatissimum) oil on microbial β-glucuronidase activity and concentration of the mammalian lignan enterolactone in ruminal fluid, plasma, urine and milk of dairy cows

Abstract: Ruminal microbiota plays an important role in the conversion of plant lignans into mammalian lignans. The main mammalian lignan present in the milk of dairy cows fed flax products is enterolactone (EL). The objectives of the present study were to investigate the effects of abomasal infusion of flax oil on the metabolism of flax lignans and concentrations of EL in biological fluids of dairy cows. A total of six rumen-cannulated dairy cows were assigned within a 2 £ 3 factorial arrangement of six treatments util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
6
0
3
Order By: Relevance
“…Previous results have demonstrated that the main site of mammalian lignan formation in ruminant animals was the rumen [18]. Indeed, increased levels of the mammalian lignan EL in ruminal fluid of cows supplemented with flax hulls [7], [36] and sheep infused with purified SDG in the rumen [17] have been reported earlier. Feed ingredients such as soy and corn contain lignans [37], [38] also lead to EL production [39], which may explain why EL was present in the rumen of cows fed CON.…”
Section: Discussionmentioning
confidence: 64%
“…Previous results have demonstrated that the main site of mammalian lignan formation in ruminant animals was the rumen [18]. Indeed, increased levels of the mammalian lignan EL in ruminal fluid of cows supplemented with flax hulls [7], [36] and sheep infused with purified SDG in the rumen [17] have been reported earlier. Feed ingredients such as soy and corn contain lignans [37], [38] also lead to EL production [39], which may explain why EL was present in the rumen of cows fed CON.…”
Section: Discussionmentioning
confidence: 64%
“…The increase in the amounts of flaxseed in food has been directly related with a higher concentration of enterolactone in plasma, urine and milk in dairy cattle [ 4 , 32 ]. In this study, we present for the first time a direct correlation between the amount of whole flaxseed added to the diet and the concentration of enterodiol and enterolactone found in sheep plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted with lactating dairy cows showed no relationship between flaxseed supplementation (FH or FM) and activity of microbial β-glucuronidase in the rumen [8,10,47], thus suggesting that this enzyme has little or no involvement in the ruminal absorption of EL, possibly because conjugation occurs during or after cell uptake of enterolignans [43]. In fact, when the ruminal activity of microbial β-glucuronidase decreased in dairy cows fed FH [48], the concentrations of EL in rumen, plasma, urine, and milk increased compared with the control diet. However, additional research is needed to elucidate the actual mechanisms involved in the absorption of enterolignans in ruminant animals.…”
Section: Metabolism Of Lignans In the Gastrointestinal Tractmentioning
confidence: 99%
“…These results [8] imply that ruminal bacteria with predominant β-glucuronidase activity may be more susceptible to the toxic effects of FO than those primarily involved in the conversion of SDG to EL as the concentration of EL in the rumen was not affected by the site of FO supplementation (rumen or abomasum). Compared with the control treatment, fecal β-glucuronidase activity tended to increase in dairy cows fed FH and no change was detected with abomasal infusion of FO in another experiment [48]. In contrast, it was found that feeding FM and infusing sunflower oil (n-6 PUFA source) in the abomasum of lactating dairy cows decreased fecal β-glucuronidase activity relative to the control treatment [47].…”
Section: Metabolism Of Lignans In the Gastrointestinal Tractmentioning
confidence: 99%
See 1 more Smart Citation